7(2x-10)+6x=10(5x-20)

Simple and best practice solution for 7(2x-10)+6x=10(5x-20) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(2x-10)+6x=10(5x-20) equation:



7(2x-10)+6x=10(5x-20)
We move all terms to the left:
7(2x-10)+6x-(10(5x-20))=0
We add all the numbers together, and all the variables
6x+7(2x-10)-(10(5x-20))=0
We multiply parentheses
6x+14x-(10(5x-20))-70=0
We calculate terms in parentheses: -(10(5x-20)), so:
10(5x-20)
We multiply parentheses
50x-200
Back to the equation:
-(50x-200)
We add all the numbers together, and all the variables
20x-(50x-200)-70=0
We get rid of parentheses
20x-50x+200-70=0
We add all the numbers together, and all the variables
-30x+130=0
We move all terms containing x to the left, all other terms to the right
-30x=-130
x=-130/-30
x=4+1/3

See similar equations:

| -1/5x+8=-22 | | 2(x-4)+5x=7x+5 | | 2×59+18+y=180 | | |3b+1|=10 | | -7p-8=-7(7p-5)-p | | 2/e-4–4/e+3=0 | | y+2×59+18=180 | | 38=7k=8k+32 | | 13-13p=5(3+2p) | | y+(2×59+18)=180 | | 3(4x+5)=17x+1-5x+14 | | 3i-2(3i-8)=8-(i+4) | | 9(8d-5)+13=12d-3 | | 58s=50 | | -4x+6=-1+4x+7 | | -4b^2+6b+28=0 | | y+(2(59)+18)=180 | | 2x-6+1=x-5+x | | 4x+5-10x=2x+20-40x | | 23=-5(7k+8) | | y+(59-15)=180 | | -10+x=2x-5 | | 4u+8=88u= | | 5(−3k−7)+(3=k+21) | | 20x-40=10(2x-4) | | x²-30x–400=0 | | 20+m=-36 | | y+59-15=180 | | -(5x-0.4)=-7(-0.4-x) | | 9(2-x)=4x-9 | | 7x+33x-5=10(4x+10) | | 3.6w=1.6w24 |

Equations solver categories